Experimental Study of Sugarcane Bagasse Ash as Partial Replacement of Cement Based on SEM and XRF Analysis - Kultida Bunjongsiri; Jirat Bunjongsiri; Anunya Pradidthaprecha; Kankanit Khwanpruk (Key engineering materials, 2024)
This research aims to identify chemical composition and it’s leaching from concrete mixed with sugarcane bagasse ash. By manipulating percent of slump flow at 110±5%, sugarcane bagasse ash was employed as a pozzolanic material to partially replace cement at 0, 10, 20, 30, 40, and 50 percent by weight of binder in concrete. Cube specimens were cast and cured in water for 3, 7, 14 and, 28 days, respectively. The patterns of sugarcane bagasse ash morphology were performed by using Scanning Electron Microscope (SEM) to analyze physicochemical characteristics. Results of tests on the X-ray fluorescence (XRF) analysis from the ash and curing water at various times revealed that SiO 2 made up half of the components in sugarcane bagasse ash. Al 2 O 3 , CaO, Fe 2 O 3 , K 2 O, P 2 O 5 , and MgO were the minor components. The calcium content from the 14-day period at 50% by weight of the sugarcane bagasse ash binder was higher than that of the other elements, according to the results of curing water. According to the results of 28-day water curing, potassium outnumbered all other elements in the replacement of sugarcane bagasse ash in every ratio.
Keywords: Concrete and Cement Materials Research; Recycling and utilization of industrial and municipal waste in materials production; Material Selection and Properties